Perceptions and beliefs of recreational anglers about Murray Cod (Maccullochella peelii) fishing in Victoria, Australia: A path to enhancing education and outreach - Andy J. Danylchuk; Taylor L. Hunt; Lucas P. Griffin; Andrew Howarth; Sascha Clark Danylchuk; Steven J. Cooke; Meaghan L. Guckian (Fisheries Research, 2026)

Hooking injury, physiological stress, and post-release activity patterns of giant trevally (Caranx ignobilis) captured using spinning gear in a catch-and-release recreational fishery - Andy J. Danylchuk; Luc LaRochelle; Graham D. Raby; Brian Bennett; Steven J. Cooke; Jacob W. Brownscombe (Environmental Biology of Fishes, 2026)

Assessment of contaminant concentrations and nutritional value of New Caledonian seaweeds - Laura Lagourgue; Claude E. Payri; Mayalen Zubia; Vincent Robert; Matthieu Waeles; Mathew A. Vanderklift; Andy Steven; Lydiane Mattio (Marine Pollution Bulletin, 2025)

On the behavior of Fish Released Following Fisheries Capture: Methods, Endpoints, and Consequences - Luc LaRochelle; Lucas P. Griffin; Jacob W. Brownscombe; Chris K. Elvidge; Caleb T. Hasler; Jessica A. Robichaud; Jamie C. Madden; Sean J. Landsman; Vincent Raoult; Andy J. Danylchuk; Steven J. Cooke (Reviews in Fisheries Science & Aquaculture, 2025)

Interdisciplinary solutions to enable nature-based solutions for coastal protection achieve ecological and engineering outcomes - Alice J. Twomey; Katherine Erickson; Melanie J. Bishop; Kris Boody; David P. Callaghan; Toni Cannard; Catherine E. Lovelock; Mariana Mayer-Pinto; Rebecca L. Morris; Andrew W.M. Pomeroy; Megan I. Saunders; Andy Steven; et al. (Environmental Science & Policy, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Synthesising Support for the Entrainment Hypothesis Through Spatially Explicit Life Cycles, Vagrancy and Collapse of Atlantic Tarpon ( Megalops atlanticus ) - Lucas P. Griffin; Aaron J. Adams; Jacob W. Brownscombe; Steven J. Cooke; Michael A. Dance; Susan K. Lowerre‐Barbieri; Eric S. Orbesen; Derke Snodgrass; Andy J. Danylchuk (Fish and Fisheries, 2025)
Understanding spatial dynamics and migratory behaviours of fish populations is essential for effective fisheries management. We focus on the migratory Atlantic tarpon ( Megalops atlanticus ) to explore how movement strategies and spatial life cycle patterns shape stock dynamics, contingent structure and mechanisms for collapse and recovery. The entrainment hypothesis posits that migratory routes are socially transmitted from experienced repeat spawners to younger conspecifics, resulting in distinct contingents within a population. Using a combination of literature review, life history data, mark‐and‐recapture records and electronic tagging, we evaluated five biological hypotheses related to entrainment mechanisms, habitat conservatism and phenotypic plasticity within Atlantic tarpon populations. Our findings provide evidence for migratory connectivity and the role of entrainment in shaping Atlantic tarpon contingent structure across the Western Atlantic. Movement and mark‐and‐recapture data revealed spatially discrete contingents with some intermixing, highlighting behavioural conservatism and phenotypic plasticity. Examples of vagrancy showed Atlantic tarpon caught far from their capture contingent, suggesting vagrant movements may contribute to colonising new habitats under suitable conditions. Straying by a subset of individuals may also increase the recovery and resilience of Atlantic tarpon stocks following collective memory loss in migratory routes. Research on contingent structure, larval recruitment patterns and abundance trends is needed to inform management measures to ensure the maintenance of migratory knowledge. This approach provides a framework for understanding Atlantic tarpon and other migratory marine fish stock dynamics, while underscoring the importance of coordinated management and conservation efforts across contingent boundaries.

Effects of capture and handling on striped bass (Morone saxatilis) in the recreational fishery of coastal Massachusetts - Olivia T. Dinkelacker; Grace A. Casselberry; Lucas P. Griffin; Sascha Clark Danylchuk; Steven J. Cooke; Andy J. Danylchuk (Fisheries Research, 2025)

Migratory patterns and seasonal habitat use of great hammerhead sharks ( Sphyrna mokarran ) in the southeastern United States - Grace A. Casselberry; Gregory B. Skomal; Lucas P. Griffin; Jacob W. Brownscombe; John T. Finn; Joseph Dello Russo; Alex Filous; Peter E. Holder; Ben Daughtry; Jeff Kneebone; Danielle Morley; Susan K. Lowerre‐Barbieri; et al. (Journal of Fish Biology, 2025)
The great hammerhead shark ( Sphyrna mokarran ) is a highly mobile shark species whose population in the United States declined dramatically through the early 2000s. Their spatial ecology is poorly understood, creating challenges for effective conservation of this enigmatic marine predator. Using acoustic telemetry and network analyses, we describe the movement patterns of 15 mature great hammerhead sharks (207–331.5 cm fork length) primarily within the waters of the southeastern United States from April 2019 to December 2022, including identifying movement corridors, core use areas and seasonal shifts in habitat use. Great hammerheads exhibited partial migration; some sharks undertook consistent, repeatable, round‐trip migrations between the tagging site in the Florida Keys and northern points in the Gulf of Mexico and Atlantic coast. Conversely, others remained in the Florida Keys year‐round. Network analysis coupled with community detection algorithms revealed that individual great hammerheads displayed oceanic basin affinity, favouring migration to either the Atlantic Ocean or Gulf of Mexico. Great hammerheads that remained in the Florida Keys shifted their habitat use seasonally from inshore channels (spring and summer) to offshore artificial reefs and the natural reef tract (summer through winter). These shifts may be driven by prey availability, as core use areas often corresponded to known locations of seasonal spawning aggregations for reef fish. These data fill an important knowledge gap for great hammerhead migratory patterns that can improve spatial management strategies for this historically overexploited species. We discuss the importance of drawing upon data from multiple tagging locations for highly mobile species management, particularly in the designation of essential fish habitat.

Free Falling: Fizzing Wild‐Caught Smallmouth Bass Results in the Inability to Control Buoyancy in Deep Water - Jamie C. Madden; Luc LaRochelle; Alyssa M. Goodenough; Andy J. Danylchuk; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Fizzing, a somewhat controversial technique for mitigating barotrauma, uses hollow hypodermic needles to release gas from the swim bladder of fish. To isolate effects of fizzing, 106 smallmouth bass ( Micropterus dolomieu ) were caught from shallow water without barotrauma and tested to determine if they could effectively control their buoyancy after having their swim bladder fizzed or punctured by releasing them over shallow (10 m) or unsuitably deep (55 m) habitat. Depth and behavior were monitored with biologgers. Most fizzed (57%) and punctured (61%) fish were unable to regulate their buoyancy in deepwater, sinking to the bottom and appearing moribund. In shallow water, punctured smallmouth bass stayed higher in the water column (like controls), while many fizzed fish stayed on the bottom. Our results suggest that if smallmouth bass are fizzed and immediately released, precautions should be taken to ensure they are released in areas of appropriate water depths (

Site-specific post-release predation of bonefish (Albula glossodonta) in a catch-and-release recreational fishery: informing voluntary actions and management strategies for a Blue Economy - Lucas P. Griffin; Gail Fordham; George Curd; Sascha Clark Danylchuk; Christopher Narty; Eleanor Brighton; Steven J. Cooke; Andy J. Danylchuk (Fisheries Research, 2025)

Physiological response of milkfish ( Chanos chanos ) to capture in a fly fishing catch‐and‐release recreational fishery - Andy J. Danylchuk; Lucas P. Griffin; Michael Lawrence; Sascha Clark Danylchuk; Eleanor Brighton; Gail Fordham; George Curd; Kyle Simpson; Devan Vd Merwe; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Recreational angling for novel marine species and related tourism development can be important in a Blue Economy. The milkfish ( Chanos chanos ) is growing in popularity as a target of fly fishing‐based catch‐and‐release (C&R) recreational fisheries, largely because of their challenge to catch and powerful swimming abilities, resulting in fight times that can exceed 1 h. Anecdotal sentiments by anglers claim that milkfish can fight for long periods of time because they do not accumulate blood lactate. To test this hypothesis, we measured blood lactate and blood glucose for 21 milkfish caught by fly fishing in the remote Alphonse Group of islands, Republic of Seychelles. Fight times ranged 5–78.3 min. Blood lactate and blood glucose concentrations increased with fight times that did not exceed 60 min. Total length of milkfish was not correlated to blood lactate or blood glucose concentrations. Ours is the first study on C&R of milkfish that debunks the anecdote that milkfish can fight for long periods of time because they do not accumulate blood lactate. Our study also revealed that milkfish may begin to physiologically recover after fight times longer than 60 min. In the context of C&R, our study indicates that anglers should limit fight times to 20–30 min when possible to reduce angling‐induced physiological stress and other potential impacts (e.g., depredation) on milkfish in recreational fisheries.

Influence of four hook types across four hook removal tools, including bare hands, on the effectiveness of hook removal and reflex impairment of Bluegill ( Lepomis macrochirus ) captured from a lake in Eastern Ontario - Jeremy Hussey; Luc LaRochelle; Andy J. Danylchuk; Sascha Clark Danylchuk; Benjamin W. C. Cooke; Joshua T. H. Cooke; Cameron J. A. Cooke; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Hook removal devices have been developed to enable rapid release of angled fish, yet little research has evaluated their effectiveness and potential for injury among hook types. We compared the performance of hook removal tools and bare hands with four hook types on freshwater Lepomid sunfish. Dehooking performance was assessed using hook removal time, unhooking difficulty, degree of tissue damage at the hooking location, and immediate reflex impairment. Unhooking difficulty was positively related to hooking depth. Unhooking difficulty was lowest for hemostats and the mechanical dehooking device; however, the mechanical dehooking device caused the largest tearing of mouth tissue. Unhooking difficulty was the main driver for hook removal time, tissue tear length, and overall reflex impairment. Hooks that were harder to remove caused higher reflex impairment. Hook type had little influence on the effectiveness of hook removal tools, although circle hooks were more difficult to remove and caused greater injury when using tools. Although use of hook removal tools can be beneficial for fish that are released, more research is needed on more species targeted by recreational anglers, and more hook removal tools. We suggest that hemostats should be used to remove hooks from fish to reduce unhooking difficulty, tissue tears, long air exposure, and thereby to increase the welfare of the fish.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Effects of Recreational Fishing Gear Type on Reflex Impairment and Post‐Release Swimming Activity of Smallmouth Bass - Luc LaRochelle; Joseph Bernardi; Jamie C. Madden; Jacob W. Brownscombe; Alyssa M. Goodenough; Andy J. Danylchuk; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Recreational anglers have access to a diverse range of rod and line strengths that enable them to choose equipment that can enhance their ability to effectively target and capture specific fish of a given body size. However, anglers may not always select the appropriate gear type for the targeted species. Here, we assessed the effect of gear setup on immediate reflex impairment and short‐term post‐release swimming behavior of Smallmouth Bass ( Micropterus dolomieu ) for 10‐min. Smallmouth Bass were caught by angling in water temperatures of 22.7°C–26.2°C using ultralight or medium spinning gear. Fight times were longer for fish captured on ultralight gear than medium gear, and fight times were longer for larger fish. Generally, fight times > 18 s resulted in one or more immediate reflex impairments, while fish with fight times

A roadmap to coastal and marine ecological restoration in Australia - Megan I. Saunders; Toni Cannard; Mibu Fischer; Marian Sheppard; Alice Twomey; Rebecca Morris; Melanie J. Bishop; Mariana Mayer-Pinto; Fiona Malcolm; Maria Vozzo; Andy Steven; Stephen E. Swearer; et al. (Environmental Science & Policy, 2024)

Inherited terrestrial cosmogenic nuclides in landscapes of selective glacial erosion: lessons from Lochnagar, Eastern Grampian Mountains, Scotland - Adrian M. Hall; David E. Sugden; Steven A. Binnie; Andy Hein; Tibor Dunai; Benedikt Ritter; Margaret Stewart (Journal of Quaternary Science, 2024)
Inheritance from prior exposure often complicates the interpretation of terrestrial cosmogenic nuclide (TCN) inventories in glaciated terrain. Lochnagar, a mountain in eastern Scotland, holds a clear geomorphological record of corrie glaciation and the thinning of the last Scottish ice sheet over the last ~15 ka. Yet attempts to date the main stages in deglaciation after sampling of 21 granite boulders for 10 Be, 26 Al and 14 C from corrie moraines, an ice sheet lateral moraine and boulder spreads revealed widespread, but variable, TCN inheritance. Only the youngest boulder ages fit within the range of expected deglaciation ages. To identify the sources of geological uncertainty, we provide simple models of ice cover duration and erosion histories for plateau, corrie and strath landscape domains, identify the variable nuclide inheritance that derives from different sources for boulders in these domains, and outline the effects of rotation, splitting and erosion of boulders during glacial transport. The combined effects increase clustering around arbitrary mean TCN values that exceed deglaciation ages. A further implication is that boulders have survived beneath overriding ice sheets. Such boulder trapping at Lochnagar may have resulted from topographic controls on katabatic winds and surface ablation acting on a thinning, cold‐based ice sheet.

The evolutionary dynamics of hyperparasites - Graham R. Northrup; Andy White; Steven R. Parratt; Carly Rozins; Anna-Liisa Laine; Mike Boots (Journal of Theoretical Biology, 2024)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Individual variation and repeatability of Atlantic tarpon Megalops atlanticus migrations in the southern US: implications for conservation and management - Lucas P. Griffin; Jacob W. Brownscombe; Aaron J. Adams; JoEllen K. Wilson; Grace A. Casselberry; Peter E. Holder; Alex Filous; Susan K. Lowerre-Barbieri; Steven J. Cooke; Andy J. Danylchuk (Marine Biology, 2023)

A recipe for plastic: Expert insights on plastic additives in the marine environment - Thomas Maes; Fiona Preston-Whyte; Stephanie Lavelle; Alessio Gomiero; Andy M. Booth; Maria Jesus Belzunce-Segarra; Juan Bellas; Steven Brooks; Adil Bakir; Lisa I. Devriese; Christopher Kim Pham; Bavo De Witte (Marine Pollution Bulletin, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Air-stagnation episodes based on regional climate models part I: evaluation over Europe - Joren Van Nieuwenhuyse; Bert Van Schaeybroeck; Steven Caluwaerts; Jonathan De Deyn; Andy Delcloo; Rozemien De Troch; Rafiq Hamdi; Piet Termonia (Climate Dynamics, 2023)

Dispersal of the pesticide diuron in the Great Barrier Reef - Jennifer Skerratt; Mark E. Baird; Mathieu Mongin; Robin Ellis; Rachael A. Smith; Melanie Shaw; Andy D.L. Steven (Science of The Total Environment, 2023)

Angler and guide perceptions provide insights into the status and threats of the Atlantic tarpon (Megalops atlanticus) fishery - Lucas P. Griffin; Grace A. Casselberry; Ezra M. Markowitz; Jacob W. Brownscombe; Aaron J. Adams; Bill Horn; Steven J. Cooke; Andy J. Danylchuk (Marine Policy, 2023)

The effectiveness of bite-shortened hooks for reducing handling time and injury of small-bodied freshwater fish captured by recreational anglers - Tara M. Lepine; William M. Twardek; Brooke Etherington; Mike Dusevic; Luc LaRochelle; Andy J. Danylchuk; Steven J. Cooke (Fisheries Research, 2023)

Conservation connections: incorporating connectivity into management and conservation of flats fishes and their habitats in a multi-stressor world - Aaron Adams; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2023)

Short-term space use of small-bodied fish in coastal flats ecosystems in The Bahamas: an acoustic telemetry study using the smallest commercially available transmitters - Petra Szekeres; Adogbeji V. Agberien; Melissa Dick; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2023)

Correction to: Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Spatial-temporal patterns of Permit (Trachinotus falcatus) habitat residency in the Florida Keys, USA - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; Ross Boucek; Aaron J. Adams; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2023)

Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Correction to: Assessing the potential for red tide (Karenia brevis) algal bloom impacts on Atlantic tarpon (Megalops atlanticus) along the southwestern coast of Florida - Lucas P. Griffin; Claudia Friess; Micah D. Bakenhaster; Kim Bassos‑Hull; Sarah Walters Burnsed; Jacob W. Brownscombe; Steven J. Cooke; Robert D. Ellis; Jayne M. Gardiner; James Locascio; Susan Lowerre‑Barbieri; Gregg R. Poulakis; et al. (Environmental Biology of Fishes, 2023)

Assessing the potential for red tide (Karenia brevis) algal bloom impacts on Atlantic tarpon (Megalops atlanticus) along the southwestern coast of Florida - Lucas P. Griffin; Claudia Friess; Micah D. Bakenhaster; Kim Bassos-Hull; Sarah Walters Burnsed; Jacob W. Brownscombe; Steven J. Cooke; Robert D. Ellis; Jayne M. Gardiner; James Locascio; Susan Lowerre-Barbieri; Gregg R. Poulakis; et al. (Environmental Biology of Fishes, 2023)

There’s no place like home: high site fidelity and small home range of bonefish (Albula vulpes) inhabiting fringing reef flats in Culebra, Puerto Rico - Lucas P. Griffin; Jacob W. Brownscombe; Tyler O. Gagné; Christopher R. Haak; Roxann Cormier; Sarah L. Becker; Steven J. Cooke; John T. Finn; Andy. J. Danylchuk (Environmental Biology of Fishes, 2023)

Are we any closer to understanding why fish can die after severe exercise? - Peter Elliot Holder; Chris M. Wood; Michael J. Lawrence; Timothy D. Clark; Cory D. Suski; Jean‐Michel Weber; Andy J. Danylchuk; Steven J. Cooke (Fish and Fisheries, 2022)
Post‐exercise mortality (PEM) may occur when fish exercise to exhaustion and are pushed so far beyond their physiological limits that they can no longer sustain life. Although fish exercise to overcome a variety of natural challenges, the phenomenon of PEM is most often observed as the result of interactions between fish and humans. The seminal work of Black (Can J Fish Aquat Sci, 15:573, 1958) and Wood et al. (J Fish Biol, 22:189, 1983) provided a foundation for exploring the potential causes of PEM in fish. With no “silver bullet” explaining PEM being apparent, contemporary research has continued to focus on physiological mechanisms of exhaustion in fish, including factors such as oxygen delivery, ion regulation, hormone signalling, and cardiac function. This paper provides an overview of these studies, and reviews the continuous improvement in data collection methods, tools, and experimental protocols used to examine the PEM phenomenon. These studies of exhaustion have played an important role in informing management actions for activities such as bycatch revival and fish passage. Since the contribution of Wood et al. (Journal of Fish Biology, 22(2):189–201, 1983), the combined efforts of fundamental and applied research have yielded a greater understanding of why fish die after severe exercise, yet much remains to be explored through future work.

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

An energetics–performance framework for wild fishes - Jacob W. Brownscombe; Graham D. Raby; Karen J. Murchie; Andy J. Danylchuk; Steven J. Cooke (Journal of Fish Biology, 2022)
There is growing evidence that bioenergetics can explain relationships between environmental conditions and fish behaviour, distribution and fitness. Fish energetic needs increase predictably with water temperature, but metabolic performance ( i.e ., aerobic scope) exhibits varied relationships, and there is debate about its role in shaping fish ecology. Here we present an energetics–performance framework, which posits that ecological context determines whether energy expenditure or metabolic performance influence fish behaviour and fitness. From this framework, we present testable predictions about how temperature‐driven variability in energetic demands and metabolic performance interact with ecological conditions to influence fish behaviour, distribution and fitness. Specifically, factors such as prey availability and the spatial distributions of prey and predators may alter fish temperature selection relative to metabolic and energetic optima. Furthermore, metabolic flexibility is a key determinant of how fish will respond to changing conditions, such as those predicted with climate change. With few exceptions, these predictions have rarely been tested in the wild due partly to difficulties in remotely measuring aspects of fish energetics. However, with recent advances in technology and measurement techniques, we now have a better capacity to measure bioenergetics parameters in the wild. Testing these predictions will provide a more mechanistic understanding of how ecological factors affect fish fitness and population dynamics, advancing our knowledge of how species and ecosystems will respond to rapidly changing environments.

Digital fisheries data in the Internet age: Emerging tools for research and monitoring using online data in recreational fisheries - Robert J. Lennox; Valerio Sbragaglia; Knut Wiik Vollset; Lene K. Sortland; Loren McClenachan; Ivan Jarić; Meaghan L. Guckian; Keno Ferter; Andy J. Danylchuk; Steven J. Cooke; Robert Arlinghaus; William M. Twardek (Fish and Fisheries, 2022)
Recreational fisheries are diverse in scale, scope, and participation worldwide, constituting an important ecosystem service of marine and freshwater ecosystems. Management of these socio‐ecological systems is challenged by monitoring gaps, stemming from difficulties engaging with participants, biased sampling, and insufficient resources to conduct biological or social surveys of fish and human populations. In the Internet age, online data have great potential to make a meaningful contribution to recreational fisheries research, monitoring, and management. Recreational fishers in some countries increasingly use social and other digital media to share their experiences with followers, with most data freely available to web scrapers that compile databases of text (e.g. tweets, status updates, comments), photos, videos and other media that contain information about spatiotemporal activity, sentiments towards catches/experiences, targeted and bycatch species, effort levels, and more. Although the future of recreational fisheries research, monitoring and management will likely involve more digital scraping, uptake is only just beginning and there are several challenges including tool availability/accessibility, sampling biases, and making findings relevant and usable to practitioners. Despite these challenges, we envision fisheries managers will increasingly turn towards online sources of fisheries data to supplement conventional methods. We challenge scientists to work towards continued method development and validation of various digital fisheries data tools and emphasize how biases from the online behaviour of users may complicate interpretations of these data for fisheries management.

The relative importance of COVID‐19 pandemic impacts on biodiversity conservation globally - David W. Gibbons; Chris Sandbrook; William J. Sutherland; Rezvin Akter; Richard Bradbury; Steven Broad; Andy Clements; Humphrey Q. P. Crick; Joanna Elliott; Ngawang Gyeltshen; Melanie Heath; Jonathan Hughes; et al. (Conservation Biology, 2022)
The COVID‐19 pandemic has had an enormous impact on almost all aspects of human society and endeavor; the natural world and its conservation have not been spared. Through a process of expert consultation, we identified and categorized, into 19 themes and 70 subthemes, the ways in which biodiversity and its conservation have been or could be affected by the pandemic globally. Nearly 60% of the effects have been broadly negative. Subsequently, we created a compendium of all themes and subthemes, each with explanatory text, and in August 2020 a diverse group of experienced conservationists with expertise from across sectors and geographies assessed each subtheme for its likely impact on biodiversity conservation globally. The 9 subthemes ranked highest all have a negative impact. These were, in rank order, governments sidelining the environment during their economic recovery, reduced wildlife‐based tourism income, increased habitat destruction, reduced government funding, increased plastic and other solid waste pollution, weakening of nature‐friendly regulations and their enforcement, increased illegal harvest of wild animals, reduced philanthropy, and threats to survival of conservation organizations. In combination, these impacts present a worrying future of increased threats to biodiversity conservation but reduced capacity to counter them. The highest ranking positive impact, at 10, was the beneficial impact of wildlife‐trade restrictions. More optimistically, among impacts ranked 11‐20, 6 were positive and 4 were negative. We hope our assessment will draw attention to the impacts of the pandemic and, thus, improve the conservation community's ability to respond to such threats in the future.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Technological innovations in the recreational fishing sector: implications for fisheries management and policy - Steven J. Cooke; Paul Venturelli; William M. Twardek; Robert J. Lennox; Jacob W. Brownscombe; Christian Skov; Kieran Hyder; Cory D. Suski; Ben K. Diggles; Robert Arlinghaus; Andy J. Danylchuk (Reviews in Fish Biology and Fisheries, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Novel deep-water spawning patterns of bonefish (Albula vulpes), a shallow water fish - Steven M. Lombardo; Aaron J. Adams; Andy J. Danylchuk; Cameron A. Luck; Matthew J. Ajemian (Marine Biology, 2020)

Hook disgorgers remove deep hooks but kill fish: A plea for cutting the line - Steven J. Cooke; Andy J. Danylchuk (Fisheries Management and Ecology, 2020)
Recreational fishing can result in deep hooking (e.g. in the gullet) of fish that are intended to be released, leading to the development of various tools intended to assist with hook removal. So‐called “hook disgorgers” are typically marketed as being a mechanism to retrieve the hook while doing so in a way that reduces harm to the fish, despite there being many studies that demonstrate that it is best to cut the line for deeply hooked fish. A study was designed to test the effectiveness of six different hook disgorgers for deeply hooked smallmouth bass, Micropterus dolomieu Lacépède, captured using baitholder hooks relative to shallow hooked controls and fish for which the line was cut. Reflex impairment and survival at 10 min, 1 hr and 24 hr were assessed. The study was terminated after early results revealed that all but one of the fish that had the hook removed died ( n = 17), while all fish that were hooked in the jaw ( n = 4) or had the line cut ( n = 5) survived. The ethical conundrum faced by the research team is discussed here, recognising that an incomplete study would have less statistical rigour even though it was very clear that disgorgers used when hooks were in the gullet killed the fish. Stopping rules are common in pharmaceutical trials and can also be used to inform catch‐and‐release research to maintain fish welfare. Best practices for anglers include cutting the line when fish are hooked in the gullet, and changing fishing strategies and gear type when deep hooking is encountered on a routine basis, otherwise mortality can be unnecessarily high.

Knowledge Gaps and Management Priorities for Recreational Fisheries in the Developing World - Shannon D. Bower; Øystein Aas; Robert Arlinghaus; T. Douglas Beard; Ian G. Cowx; Andy J. Danylchuk; Kátia M. F. Freire; Warren M. Potts; Stephen G. Sutton; Steven J. Cooke (Reviews in Fisheries Science & Aquaculture, 2020)

Application of machine learning algorithms to identify cryptic reproductive habitats using diverse information sources - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; John Hunt; Susan K. Lowerre-Barbieri; Aaron J. Adams; Andy J. Danylchuk; Steven J. Cooke (Oecologia, 2020)

The spawning migrations of an exploited Albulid in the tropical Pacific: implications for conservation and community-based management - Alexander Filous; Robert J. Lennox; Raphael Raveino; Alan M. Friedlander; Eric E. G. Clua; Steven J. Cooke; Andy J. Danylchuk (Environmental Biology of Fishes, 2020)

Best practices for non‐lethal blood sampling of fish via the caudal vasculature - Michael J. Lawrence; Graham D. Raby; Amy K. Teffer; Ken M. Jeffries; Andy J. Danylchuk; Erika J. Eliason; Caleb T. Hasler; Timothy D. Clark; Steven J. Cooke (Journal of Fish Biology, 2020)
Blood sampling through the caudal vasculature is a widely used technique in fish biology for investigating organismal health and physiology. In live fishes, it can provide a quick, easy and relatively non‐invasive method for obtaining a blood sample ( cf . cannulation and cardiac puncture). Here, a general set of recommendations are provided for optimizing the blood sampling protocol that reflects best practices in animal welfare and sample integrity. This includes selecting appropriate use of anaesthetics for blood sampling as well as restraint techniques for situations where sedation is not used. In addition, ideal sampling environments where the fish can freely ventilate and strategies for minimizing handling time are discussed. This study summarizes the techniques used for extracting blood from the caudal vasculature in live fishes, highlighting the phlebotomy itself, the timing of sampling events and acceptable blood sample volumes. This study further discuss considerations for selecting appropriate physiological metrics when sampling in the caudal region and the potential benefits that this technique provides with respect to long‐term biological assessments. Although general guidelines for blood sampling are provided here, it should be recognized that contextual considerations ( e.g. , taxonomic diversity, legal matters, environmental constraints) may influence the approach to blood sampling. Overall, it can be concluded that when done properly, blood sampling live fishes through the caudal vasculature is quick, efficient and minimally invasive, thus promoting conditions where live release of focal animals is possible.

Bacterial communities on the gills of bonefish (Albula vulpes) in the Florida Keys and The Bahamas show spatial structure and differential abundance of disease-associated bacteria - Christopher D. Dunn; Lewis J. Campbell; Elizabeth M. Wallace; Andy J. Danylchuk; Steven J. Cooke; Aaron D. Shultz; Brooke D. Black; Jacob W. Brownscombe; Lucas P. Griffin; David P. Philipp; Aaron J. Adams; Tony L. Goldberg (Marine Biology, 2020)

Population dynamics of roundjaw bonefish Albula glossodonta at a remote coralline Atoll inform community‐based management in an artisanal fishery - Alexander Filous; Robert J. Lennox; Paige Eveson; Raphael Raveino; Eric E. G. Clua; Steven J. Cooke; Andy J. Danylchuk (Fisheries Management and Ecology, 2020)
Fisheries management requires knowledge on the population dynamics of exploited stocks. To that end, the present study used a mark–recapture approach to characterise the population demographics of roundjaw bonefish Albula glossodonta (Forsskål) and their interaction with a data‐limited fishery on Anaa Atoll in the Tuamotu Archipelago of French Polynesia. Over the course of the study, 2,509 bonefish were tagged and 12.3% were recaptured. The L ∞ of bonefish was estimated at 71 cm fork length (FL) with a K of 0.17, based on changes in FL between capture events. Artisanal fish traps located in the migratory corridors of the atoll accounted for 94% of recaptures and these movements occurred during the waning moon. Fishing mortality increased as bonefish reach sexual maturity, recruiting to the trap fishery at age 4 with the onset of spawning behaviour. Bonefish abundance between ages 3 and 5 was estimated to be 29,079 individuals. This case study demonstrated the utility of mark–recapture in filling knowledge gaps that impede the management of data‐limited fisheries. Ultimately, these results supported the creation of an Educational Managed Marine Area and the resurgence of rahui (seasonal closure) to manage this fishery.

Preparing for a changing future in recreational fisheries: 100 research questions for global consideration emerging from a horizon scan - Peter E. Holder; Amanda L. Jeanson; Robert J. Lennox; Jacob W. Brownscombe; Robert Arlinghaus; Andy J. Danylchuk; Shannon D. Bower; Kieran Hyder; Len M. Hunt; Eli P. Fenichel; Paul A. Venturelli; Eva B. Thorstad; et al. (Reviews in Fish Biology and Fisheries, 2020)

Seasonal occupancy and connectivity amongst nearshore flats and reef habitats by permit Trachinotus falcatus : considerations for fisheries management - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; John Hunt; Susan K. Lowerre‐Barbieri; Glenn T. Crossin; Sara J. Iverson; Ross Boucek; Aaron J. Adams; Steven J. Cooke; Andy J. Danylchuk (Journal of Fish Biology, 2020)
We used acoustic telemetry to quantify permit Trachinotus falcatus habitat use and connectivity in proximity to the Florida Keys, USA, and assessed these patterns relative to current habitat and fisheries management practices. From March 2017 to June 2018, 45 permit tagged within 16 km of the lower Florida Keys were detected at stationary acoustic receivers throughout the south Florida region, the majority of which remained within the Special Permit Zone, where more extensive fisheries harvest regulations are implemented. There was a high level of connectivity between nearshore flats ( i.e. ,

Wetland methane emissions dominated by plant‐mediated fluxes: Contrasting emissions pathways and seasons within a shallow freshwater subtropical wetland - Luke C. Jeffrey; Damien T. Maher; Scott G. Johnston; Brendan P. Kelaher; Andy Steven; Douglas R. Tait (Limnology and Oceanography, 2019)
Wetlands represent the largest natural source of methane; however, very few studies have simultaneously quantified the three main atmospheric flux pathways (i.e., diffusive, ebullition, and plant‐mediated). Unlike better‐studied northern hemisphere systems, many Australian subtropical wetlands undergo extreme wet/dry oscillations, which may strongly impact methane dynamics. We assessed diurnal methane emissions of multiple pathways during three distinct seasonal events within an Australian freshwater wetland. Six‐fold higher methane emissions occurred during summer compared to autumn floods (which followed an extensive dry‐period) and winter/cool conditions. Over three seasons, diffusion represented the highest average areal fluxes (25.9 ± 73.2 mmol m −2 d −1 ) but were within range of fluxes through water lily aerenchyma (20.8 ± 41.5 mmol m −2 d −1 ). Average ebullition rates were 5.5 ± 9.7 mmol m −2 d −1 . Water column CH 4 displayed high spatiotemporal variability, ranging from 55.0 to 253.5 μ mol L −1 . Time series δ 13 C–CH 4 isotope measurements revealed an oxidation fraction of ~ 15% at night‐time and ~ 36% during day‐time, and night‐time diffusive fluxes were consistently ~ three‐fold higher than day‐time fluxes. By aggregating seasons and weighting for changes in lily coverage, plant‐mediated fluxes accounted for ~ 59% of the annual methane emissions, whereas ebullition and diffusion each accounted for ~ 20%. The up‐scaled annual area‐weighted wetland methane flux (combined pathways) was 27.3 ± 36.7 mmol m −2 d −1 . We contend that water lilies ( Nymphaea sp.) are the significant carbon source, mediator, and conduit for methane fluxes in this system, and the extremely large seasonal variability of methane emissions reflect dynamic redox oscillations driven by oscillating wet and dry conditions.

Mahseer (Tor spp.) fishes of the world: status, challenges and opportunities for conservation - Adrian C. Pinder; J. Robert Britton; Andrew J. Harrison; Prakash Nautiyal; Shannon D. Bower; Steven J. Cooke; Steve Lockett; Mark Everard; Unmesh Katwate; K. Ranjeet; Sam Walton; Andy J. Danylchuk; et al. (Reviews in Fish Biology and Fisheries, 2019)

Searching for responsible and sustainable recreational fisheries in the Anthropocene - Steven J. Cooke; William M. Twardek; Andrea J. Reid; Robert J. Lennox; Sascha C. Danylchuk; Jacob W. Brownscombe; Shannon D. Bower; Robert Arlinghaus; Kieran Hyder; Andy J. Danylchuk (Journal of Fish Biology, 2019)
Recreational fisheries that use rod and reel ( i.e ., angling) operate around the globe in diverse freshwater and marine habitats, targeting many different gamefish species and engaging at least 220 million participants. The motivations for fishing vary extensively; whether anglers engage in catch‐and‐release or are harvest‐oriented, there is strong potential for recreational fisheries to be conducted in a manner that is both responsible and sustainable. There are many examples of recreational fisheries that are well‐managed where anglers, the angling industry and managers engage in responsible behaviours that both contribute to long‐term sustainability of fish populations and the sector. Yet, recreational fisheries do not operate in a vacuum; fish populations face threats and stressors including harvest from other sectors as well as environmental change, a defining characteristic of the Anthropocene. We argue that the future of recreational fisheries and indeed many wild fish populations and aquatic ecosystems depends on having responsible and sustainable (R&S) recreational fisheries whilst, where possible, addressing, or at least lobbying for increased awareness about the threats to recreational fisheries emanating from outside the sector ( e.g ., climate change). Here, we first consider how the concepts of R&S intersect in the recreational fishing sector in an increasingly complex socio‐cultural context. Next, we explore the role of the angler, angling industry and decision‐makers in achieving R&S fisheries. We extend this idea further by considering the consequences of a future without recreational fisheries (either because of failures related to R&S) and explore a pertinent case study situated in Uttarakahand, India. Unlike other fisheries sectors where the number of participants is relatively small, recreational angling participants are numerous and widespread, such that if their actions are responsible, they have the potential to be a key voice for conservation and serve as a major force for good in the Anthropocene. What remains to be seen is whether this will be achieved, or if failure will occur to the point that recreational fisheries face increasing pressure to cease, as a result of external environmental threats, the environmental effects of recreational fishing and emerging ethical concerns about the welfare of angled fish.

Environmental drivers of habitat use by a marine fish on a heterogeneous and dynamic reef flat - Jacob W. Brownscombe; Lucas P. Griffin; Tyler O. Gagne; Christopher R. Haak; Steven J. Cooke; John T. Finn; Andy J. Danylchuk (Marine Biology, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

Ontogenetic patterns in resource use dynamics of bonefish (Albula vulpes) in the Bahamas - Karen J. Murchie; Christopher R. Haak; Michael Power; Oliver N. Shipley; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2019)

Estimating fish swimming metrics and metabolic rates with accelerometers: the influence of sampling frequency - Jacob W. Brownscombe; Robert J. Lennox; Andy J. Danylchuk; Steven J. Cooke (Journal of Fish Biology, 2018)
Accelerometry is growing in popularity for remotely measuring fish swimming metrics, but appropriate sampling frequencies for accurately measuring these metrics are not well studied. This research examined the influence of sampling frequency (1–25 Hz) with tri‐axial accelerometer biologgers on estimates of overall dynamic body acceleration (ODBA), tail‐beat frequency, swimming speed and metabolic rate of bonefish Albula vulpes in a swim‐tunnel respirometer and free‐swimming in a wetland mesocosm. In the swim tunnel, sampling frequencies of ≥ 5 Hz were sufficient to establish strong relationships between ODBA, swimming speed and metabolic rate. However, in free‐swimming bonefish, estimates of metabolic rate were more variable below 10 Hz. Sampling frequencies should be at least twice the maximum tail‐beat frequency to estimate this metric effectively, which is generally higher than those required to estimate ODBA, swimming speed and metabolic rate. While optimal sampling frequency probably varies among species due to tail‐beat frequency and swimming style, this study provides a reference point with a medium body‐sized sub‐carangiform teleost fish, enabling researchers to measure these metrics effectively and maximize study duration.

Fine-scale movement and activity patterns of Caribbean reef sharks (Carcharhinus perezi) in the Bahamas - Oliver N. Shipley; Jacob W. Brownscombe; Andy J. Danylchuk; Steven J. Cooke; Owen R. O’Shea; Edward J. Brooks (Environmental Biology of Fishes, 2018)

The nexus of fun and nutrition: Recreational fishing is also about food - Steven J Cooke; William M Twardek; Robert J Lennox; Aaron J Zolderdo; Shannon D Bower; Lee F G Gutowsky; Andy J Danylchuk; Robert Arlinghaus; Douglas Beard (Fish and Fisheries, 2018)
Recreational fishing is a popular activity in aquatic ecosystems around the globe using a variety of gears including rod and line and to a lesser extent handlines, spears, bow and arrow, traps and nets. Similar to the propensity to engage in voluntary catch‐and‐release, the propensity to harvest fishes strongly varies among cultures, locations, species and fisheries. There is a misconception that because recreational fishing happens during non‐work (i.e. leisure) time, the nutritional motivation is negligible; therefore, the role of recreational fishing in supporting nutrition (and thus food security) at regional, national or global scales is underappreciated. We consider the factors that influence whether fish will be harvested or released by examining the motives that underlie recreational fishing. Next, we provide an overview of the magnitude and role of recreational fishing harvest in supporting nutrition using regional case‐studies. Then, we address issues such as contaminants and parasites that constrain the ability of fish harvested by recreational fishers to be consumed. Although recreational fishing is foremost a leisure activity, the harvest of fish for personal consumption by recreational fishers has contributed and will continue to contribute to human nutrition by providing an accessible, affordable and generally highly sustainable food source, notwithstanding concerns about food safety and possibly overfishing. Attempts to better quantify the role of fish harvested by recreational fishers and the relative contribution to overall food security and personal nutrition will provide resource managers and policymakers the information needed to guide management activities and policy development.

Angling into the Future: Ten Commandments for Recreational Fisheries Science, Management, and Stewardship in a Good Anthropocene - Laura K. Elmer; Lisa A. Kelly; Stephanie Rivest; S. Clay Steell; William M. Twardek; Andy J. Danylchuk; Robert Arlinghaus; Joseph R. Bennett; Steven J. Cooke (Environmental Management, 2017)

Shark recreational fisheries: Status, challenges, and research needs - Austin J. Gallagher; Neil Hammerschlag; Andy J. Danylchuk; Steven J. Cooke (Ambio, 2017)

Spatiotemporal drivers of energy expenditure in a coastal marine fish - Jacob W. Brownscombe; Steven J. Cooke; Andy J. Danylchuk (Oecologia, 2017)

Individual-level behavioral responses of immature green turtles to snorkeler disturbance - Lucas P. Griffin; Jacob W. Brownscombe; Tyler O. Gagné; Alexander D. M. Wilson; Steven J. Cooke; Andy J. Danylchuk (Oecologia, 2017)

Agronomic Response of Crops Fertilized with Struvite Derived from Dairy Manure - Katherine Hilt; Joe Harrison; Keith Bowers; Robert Stevens; Andy Bary; Kelsey Harrison (Water, Air, & Soil Pollution, 2016)

Angling for endangered fish: conservation problem or conservation action? - Steven J Cooke; Zeb S Hogan; Paul A Butcher; Michael J W Stokesbury; Rajeev Raghavan; Austin J Gallagher; Neil Hammerschlag; Andy J Danylchuk (Fish and Fisheries, 2016)
Recreational angling has been implicated in population declines of some marine and freshwater fish, but this activity is rarely considered as a threat or even halted when endangered species are targeted. Indeed, in some cases, anglers are drawn to fish for rare or endangered species. Conservation‐oriented behaviours such as catch‐and‐release are often practiced voluntarily due to the ethics of anglers, yet even in these cases, some fishing mortality occurs. Nonetheless, there are many indirect conservation benefits associated with recreational angling. Here, we present a series of case‐studies and consider whether catch‐and‐release angling for endangered fish is a conservation problem or a conservation action. If recreational angling activities contribute to population‐level consequences that are contrary to recovery strategies, then angling for endangered species would seem to be a poor option. However, as revealed by several case‐studies, there is much evidence that anglers are vocal and effective proponents of fish and habitat conservation, and for endangered species, they are often the only voice when other stakeholders are not engaged. Anglers may contribute directly to conservation actions via user fees (e.g. licences), philanthropic donations or by volunteering in research, education and restoration activities. However, it is important to quantify post‐release mortality as well as understand the full suite of factors influencing a given population or species to know the potential risks. A risk assessment approach outlined in the paper may be used by managers to determine when the benefits of angling for endangered species outweigh the risks.

Weighting climate model ensembles for mean and variance estimates - Ned Haughton; Gab Abramowitz; Andy Pitman; Steven J. Phipps (Climate Dynamics, 2015)

Physiological stress and reflex impairment of recreationally angled bonefish in Puerto Rico - Jacob W. Brownscombe; Lucas P. Griffin; Tyler Gagne; Christopher R. Haak; Steven J. Cooke; Andy J. Danylchuk (Environmental Biology of Fishes, 2015)

Swimming energetics and thermal ecology of adult bonefish (Albula vulpes): a combined laboratory and field study in Eleuthera, The Bahamas - Liane B. Nowell; Jacob W. Brownscombe; Lee F. G. Gutowsky; Karen J. Murchie; Cory D. Suski; Andy J. Danylchuk; Aaron Shultz; Steven J. Cooke (Environmental Biology of Fishes, 2015)

Can macroalgae contribute to blue carbon? An A ustralian perspective - Ross Hill; Alecia Bellgrove; Peter I. Macreadie; Katherina Petrou; John Beardall; Andy Steven; Peter J. Ralph (Limnology and Oceanography, 2015)
Macroalgal communities in Australia and around the world store vast quantities of carbon in their living biomass, but their prevalence of growing on hard substrata means that they have limited capacity to act as long‐term carbon sinks. Unlike other coastal blue carbon habitats such as seagrasses, saltmarshes and mangroves, they do not develop their own organic‐rich sediments, but may instead act as a rich carbon source and make significant contributions in the form of detritus to sedimentary habitats by acting as a “carbon donor” to “receiver sites” where organic material accumulates. The potential for storage of this donated carbon however, is dependent on the decay rate during transport and the burial efficiency at receiver sites. To better understand the potential contribution of macroalgal communities to coastal blue carbon budgets, a comprehensive literature search was conducted using key words, including carbon sequestration, macroalgal distribution, abundance and productivity to provide an estimation of the total amount of carbon stored in temperate Australian macroalgae. Our most conservative calculations estimate 109.9 Tg C is stored in living macroalgal biomass of temperate Australia, using a coastal area covering 249,697 km 2 . Estimates derived for tropical and subtropical regions contributed an additional 23.2 Tg C. By extending the search to include global studies we provide a broader context and rationale for the study, contributing to the global aspects of the review. In addition, we discuss the potential role of calcium carbonate‐containing macroalgae, consider the dynamic nature of macroalgal populations in the context of climate change, and identify the knowledge gaps that once addressed will enable robust quantification of macroalgae in marine biogeochemical cycling of carbon. We conclude that macroalgal communities have the potential to make ecologically meaningful contributions toward global blue carbon sequestration, as donors, but given that the fate of detached macroalgal biomass remains unclear, further research is needed to quantify this contribution.

Status of Recreational Fisheries in India: Development, Issues, and Opportunities - Nishikant Gupta; Shannon D. Bower; Rajeev Raghavan; Andy J. Danylchuk; Steven J. Cooke (Reviews in Fisheries Science & Aquaculture, 2015)

Natural in situ relationships suggest coral reef calcium carbonate production will decline with ocean acidification - Emily C. Shaw; Stuart R. Phinn; Bronte Tilbrook; Andy Steven (Limnology and Oceanography, 2015)
There are few in situ studies showing how net community calcification ( G net ) of coral reefs is related to carbonate chemistry, and the studies to date have demonstrated different predicted rates of change. In this study, we measured net community production ( P net ), G net , and carbonate chemistry of a reef flat at One Tree Island, Great Barrier Reef. Diurnal p CO 2 variability of 289–724 μatm was driven primarily by photosynthesis and respiration. The reef flat was found to be net autotrophic, with daily production of ∼ 35 mmol C m −2 d −1 and net calcification of ∼ 33 mmol C m −2 d −1 . G net was strongly related to P net , which drove a hysteresis pattern in the relationship between G net and aragonite saturation state (Ω ar ). Although P net was the main driver of G net , Ω ar was still an important factor, where 95% of the variance in G net could be described by P net and Ω ar . Based on the observed in situ relationship, G net would be expected to reach zero when Ω ar is ∼ 2.5. It is unknown what proportion of a decline in G net would be through reduced calcification and what would occur through increased dissolution, but the results here support predictions that overall calcium carbonate production will decline in coral reefs as a result of ocean acidification.

Deciphering sedimentary organic matter sources: Insights from radiocarbon measurements and NMR spectroscopy - Jonathan Sanderman; Evelyn Krull; Thomas Kuhn; Gary Hancock; Janine McGowan; Todd Maddern; Stewart Fallon; Andy Steven (Limnology and Oceanography, 2015)
In a sediment core collected from an estuary in a rapidly urbanizing region in South East Queensland, Australia, we used multiple geochemical tracers to understand the provenance, form, and rate of accumulating organic matter (OM) focusing on the application of two tools often used in studies of soil OM: solid‐state 13 C nuclear magnetic resonance (NMR) spectroscopy and interpretation of radiocarbon ( 14 C) data by modeling the uptake of the bomb‐spike in atmospheric 14 C. While elemental (C, N) and stable isotope ( 13 C, 15 N) data generally could not distinguish OM sources, these data did indicate that there has been a steady increase in nutrient loading to the estuary and that there were periodic deposition events where the OM was dominated by C3 terrestrial vegetation. The NMR results showed that the OM was primarily of terrestrial origin being dominated by lignin and stable char‐like carbon compounds in all samples. The 14 C data and modeling indicated that the OM was composed of a mixture of material with widely varying ages. In general, the OM was hundreds of years older than the age of the sediments as determined by fallout radionuclide dating (1950–2009 chronology), indicating that a large fraction of the OM has resided on the terrestrial landscape for a substantial period before being transported and buried in the estuary sediments. By applying this combination of techniques, we have been able to develop a coherent picture of a very complex deposition and accumulation history in these estuary sediments.

On the generation of climate model ensembles - Ned Haughton; Gab Abramowitz; Andy Pitman; Steven J. Phipps (Climate Dynamics, 2014)

The understudied and underappreciated role of predation in the mortality of fish released from fishing gears - Graham D Raby; Jessica R Packer; Andy J Danylchuk; Steven J Cooke (Fish and Fisheries, 2014)
The assumption that animals released from fishing gears survive has frequently been scrutinized by researchers in recent years. Mortality estimates from these research efforts can be incorporated into management models to ensure the sustainability of fisheries and the conservation of threatened species. Post‐release mortality estimates are typically made by holding the catch in a tank, pen or cage for short‐term monitoring (e.g. 48 h). These estimates may be inaccurate in some cases because they fail to integrate the challenges of the wild environment. Most obvious among these challenges is predator evasion. Stress and injury from a capture experience can temporarily impair physiological capacity and alter behaviour in released animals, a period during which predation risk is likely elevated. In large‐scale commercial fisheries, predators have adapted their behaviour to capitalize on impaired fishes being discarded, while in recreational catch‐and‐release fisheries, exercise and air exposure can similarly impede the capacity for released fish to evade opportunistic predators. Owing to the indirect and often cryptic nature of this source of mortality, very few studies have attempted to document it. A survey of the literature demonstrated that

Voluntary institutions and behaviours as alternatives to formal regulations in recreational fisheries management - Steven J Cooke; Cory D Suski; Robert Arlinghaus; Andy J Danylchuk (Fish and Fisheries, 2013)
Traditional regulatory options (formal institutions) imposed by government agencies such as harvest and gear restrictions represent the standard in recreational fisheries management, at least in developed countries. However, there exist a number of alternatives including the use of angler education programmes that attempt to evoke voluntary changes in angler behaviour, resulting in the emergence of voluntarily motivated resource‐conserving informal institutions. These ‘softer’ approaches to aquatic stewardship and fisheries management can be developed in cooperation with stakeholders and in many cases are led by avid anglers and angling groups. Examples of such measures include voluntary sanctuaries, informally enforced seasonal closures, personal daily bag limits, self‐imposed constraints on gear, development of entirely live‐release fisheries, and adoption of fish and aquatic ecosystem conservation‐oriented gears and release practices. Education efforts that provide anglers with knowledge on best practices and empower them to modify their behaviour hold great promise to meet formal management goals and objectives, but seem to be underutilized relative to formal regulations. This article highlights the benefits and challenges of relying on informal institutions as alternatives to traditional regulatory options. Informal institutions that protect resources and help overfished stocks recover hold great promise in both developed and developing countries, particularly when there is a single stakeholder group or when the capacity to enforce traditional regulations or to invest in stock assessments is limited. Informal institutions may help make formal institutions more effective or can even be alternatives to costly institutions that depend on enforcement to be effective.

Spatial ecology and residency patterns of adult great barracuda (Sphyraena barracuda) in coastal waters of The Bahamas - Amanda C. O’Toole; Andy J. Danylchuk; Tony L. Goldberg; Cory D. Suski; David P. Philipp; Edd Brooks; Steven J. Cooke (Marine Biology, 2011)

Aggregations and offshore movements as indicators of spawning activity of bonefish (Albula vulpes) in The Bahamas - Andy J. Danylchuk; Steven J. Cooke; Tony L. Goldberg; Cory D. Suski; Karen J. Murchie; Sascha E. Danylchuk; Aaron D. Shultz; Christopher R. Haak; Edd J. Brooks; Annabelle Oronti; Jeff B. Koppelman; David P. Philipp (Marine Biology, 2011)

Engaging the Recreational Angling Community to Implement and Manage Aquatic Protected Areas - ANDY J. DANYLCHUK; STEVEN J. COOKE (Conservation Biology, 2011)
Recreational angling is a popular leisure activity, the quality of which is greatly dependent on fish abundance and well‐functioning aquatic ecosystems. Aquatic protected areas (APAs) are used to help maintain and even restore aquatic systems and their associated biota, including fish species that are popular with recreational anglers. Paradoxically, the use of APAs has been a source of much contention and conflict between members of the recreational angling community and those interested in or mandated to protect aquatic resources on the basis of the interests of multiple stakeholder groups. The angling community is concerned about the loss of fishing opportunities and effectiveness of APAs. Although it is still unclear whether establishment of APAs alone can effectively protect aquatic resources, actively including the recreational angling community in the design, implementation, and management of APAs will help ensure the values of this rather substantial user group are incorporated into aquatic conservation strategies. Conversely, the probability of increasing the sustainability of recreational angling and related economies will be greatest if recreational angler groups remain open minded to both short‐term and long‐term goals of fisheries conservation strategies, including the use of APAs.

Spatial ecology of juvenile lemon sharks (Negaprion brevirostris) in tidal creeks and coastal waters of Eleuthera, The Bahamas - Karen J. Murchie; Emily Schwager; Steven J. Cooke; Andy J. Danylchuk; Sascha E. Danylchuk; Tony L. Goldberg; Cory D. Suski; David P. Philipp (Environmental Biology of Fishes, 2010)

Cancer Survivorship: A New Challenge in Comprehensive Cancer Control - Lori A. Pollack; Greta E. Greer; Julia H. Rowland; Andy Miller; Donna Doneski; Steven S. Coughlin; Ellen Stovall; Doug Ulman (Cancer Causes & Control, 2005)